KEBIJAKAN FISKAL PADA MASA RASULULLAH SAW DAN RELEVANSINYA DENGAN KEBIJAKAN FISKAL MODERN DI BPKPAD TAPANULI SELATAN - Sa’adilah Mursyid Saragih; Ismail Marzuki; Sarmiana Batubara (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This research aims to analyze fiscal policy during the time of the Prophet Muhammad SAW and its relevance to modern fiscal policies implemented by the Regional Financial, Revenue, and Asset Management Agency (BPKPAD) of Tapanuli Selatan Regency. This study adopts a qualitative method with a case study approach, involving semi-structured interviews and analysis of local government official documents. The study's findings indicate that fiscal policy during the time of the Prophet Muhammad SAW was based on the principles of justice, public benefit, and equitable resource distribution, with a distribution system that prioritized meeting needs. Fiscal instruments such as zakat, ushr, kharaj, jizyah, fay’, and ghanimah were centrally managed by Baitul Mal and distributed directly to eligible recipients, thus succeeding in reducing poverty and economic inequality. In contrast, the management of modern fiscal policy by BPKPAD Tapanuli Selatan places more emphasis on administrative and legal aspects, as well as medium to long-term development planning through the Regional Revenue and Expenditure Budget (APBD). This policy is highly dependent on transfer funds from the central government and expenditure allocations that do not fully cover the priority needs of the poor. This study concludes that the principles of fiscal policy during the time of the Prophet Muhammad SAW are highly relevant for integration into modern fiscal policies, especially in strengthening the focus on social justice and designing responsive budgets to community needs to enhance the effectiveness of fiscal policy at the regional level.